Is religion or culture the key feature in changes in substance use after leaving school? Young Punjabis and a comparison group in Glasgow. - Bradby H; Williams R (Ethnicity & Health, 2006)
Aims. To establish levels of use of tobacco, alcohol and illegal drugs among 18-20 year old men and women of Asian (Punjabi) and non-Asian origin compared with levels four years earlier and consider the role of religion and culture in abstinent behaviour. Design. Structured self-complete questionnaire used with 94% of pupils with South Asian names recorded by the Greater Glasgow education department in 1991 and a proportionate random sample of pupils in the same years who did not have South Asian names. Followed up in 1996 in an interviewer-led structured questionnaire in their own homes. Setting. Greater Glasgow, largest city in the west of Scotland. Participants. Eight hundred and twenty-four overwhelmingly British-born 14-15 year olds in 1992, 492 followed up aged 18-20 years in 1996. Measurements. Self-report measures of ever having tried alcohol, tobacco and drugs and the quantities consumed at age 14-15 and 18-20. Indication of reasons for abstinence from substance use at age 18-20. Findings. Asians were much more abstinent from all these substances at both ages (p < 0.001), except for smoking at 18-20. However, religiously specific patterns of abstinence were particularly strong for alcohol (Muslim odds ratio 7- to 9-fold lower at 14-15, 16- to 25-fold lower at 18-20) and smoking (Sikh/Hindu odds ratio 10-fold lower than Muslims, 20-fold than Christians at 18-20), though there is a shared Asian tendency for women to observe these patterns more than men at 18-20. Conclusions. At age 14-15 abstinence was high in the largely British-born generation of Asians mainly for cultural reasons common to religious groups. Four years later culturally determined abstinence has atrophied, and abstinence reflects the specific influence of ascetic religious traditions, though some cultural influence remains in that women are more affected. Intergenerational changes are similar. The erosion of constraints on smoking presents a threat to health.